2019
DOI: 10.1101/600932
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrative transcriptomics reveals sexually dimorphic microRNA control of the cholinergic/neurokine interface in schizophrenia and bipolar disorder

Abstract: 135 words): RNA-sequencing analyses are often limited to identifying lowest p-value transcripts, which does not address polygenic phenomena. To overcome this limitation, we developed an integrative approach that combines large scale transcriptomic meta-analysis of patient brain tissues with single-cell sequencing data of CNS neurons, short RNA-sequencing of human male-and female-originated cell lines, and connectomics of transcription factor-and microRNA-interactions with perturbed transcripts. We used this pi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 113 publications
(141 reference statements)
0
5
0
Order By: Relevance
“…Thanks to these studies, an overview of differences in rodents is slowly building up allowing comparisons with evidence from psychiatric patients to be made. These high‐throughput studies include both microarray and RNA‐sequencing approaches. Both types of technologies allow for a genome‐wide profiling of stress responses in the two sexes and the study of these responses in the context of pathways.…”
Section: Chronic Stressmentioning
confidence: 99%
“…Thanks to these studies, an overview of differences in rodents is slowly building up allowing comparisons with evidence from psychiatric patients to be made. These high‐throughput studies include both microarray and RNA‐sequencing approaches. Both types of technologies allow for a genome‐wide profiling of stress responses in the two sexes and the study of these responses in the context of pathways.…”
Section: Chronic Stressmentioning
confidence: 99%
“…To examine the potential activity of tRFs as regulators of gene expression, we chose to focus on the cholinergic system, which tends to be impaired with age (Perry, 1980), and in neurodegenerative diseases such as PD (Bohnen & Albin, 2011). For this purpose, we defined Cholino‐tRFs as tRFs with the potential to target one core cholinergic gene (i.e., one of the enzymes responsible for the synthesis or breakdown of acetylcholine; cholinergic gene list acquired from Lobentanzer et al, 2019) or at least five genes associated with cholinergic activity in a similar manner to microRNAs (Figure 5a; prediction done by sequences complementarity between the tRFs and the targets, see Methods).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding AD, ample evidence reports sncRNAs shedding into the CSF of patients with AD. A number of miRs, such as miR‐222 and the acetylcholinesterase‐targeting miR‐125b (Lobentanzer et al, 2019), have been shown to be DE in the CSF of AD patients (Dangla‐Valls et al, 2017). Finally, DE sncRNAs have also been shown in the CSF of PD patients, where hsa‐mir‐626, for example, has been the main focus—both as a potential biomarker for disease severity and as a potential therapeutic target (Xia et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although miR-125b and miR-29b are the top-ranked AD biomarkers in several clinical studies [129][130][131], the mechanism of dysregulation in the blood of AD patients is still unclear. In silico analysis reveals that miR-125b regulates the cholinergic neuron functions by targeting Clock [132]. Further, recent evidence shows that miR-125b regulates neuronal cell growth and apoptosis via the regulation of inflammatory factors and oxidative stress, and this regulation may be related to AD pathogenesis [133].…”
Section: Alzheimer's Diseasementioning
confidence: 99%